The association between the incident risk of Parkinson’s disease and depression in middle-aged and older adults, and the moderating role of lifestyle: evidence from the CHARLS - Wei, Wu-xiao; Meng, Lian; Mao, Zhen-fang; Mo, Zhen-hua; Yang, Lu; Qin, Yan; Huang, Jin-yu (Frontiers in Psychology, 2025)
BackgroundParkinson’s disease (PD) and depression frequently coexist in middle-aged and older populations, potentially influencing each other. This study explores the relationship between depression and PD risk and investigates the association between lifestyle score and PD risk.MethodsData from the China Health and Retirement Longitudinal Study (CHARLS) for adults aged 45 and above were analyzed. A total of 30,347 participants were included, with 565 individuals developing PD during follow-up. PD cases were self-reported physician diagnoses. Depression was assessed using the CESD-10 scale (score ≥ 10 indicating depression). Lifestyle factors (smoking, drinking, social activity, sleep, and BMI) were scored as healthy (≥4) or unhealthy (<4). Cox proportional hazards models were used to analyze PD risk, and cubic spline regression was employed to evaluate the dose–response relationship between depression, lifestyle, and PD risk.ResultsDepression (CESD-10 ≥ 10) was significantly associated with an increased risk of PD. In the fully adjusted model (Model 4), individuals with depression had a 53% higher risk of developing PD compared to those without depression (HR = 1.53, 95% CI: 1.28–1.83). Cubic spline regression revealed a dose–response relationship: as CESD-10 scores increased, the risk of PD also increased. Unhealthy lifestyle was significantly associated with a higher risk of PD. The analysis showed that individuals with an unhealthy lifestyle had a 23.5% higher risk of developing PD than those with a healthy lifestyle. Additionally, the risk of PD varied with different lifestyle components. For example, no-smoking had a 17.9% lower risk of developing PD compared to smoking, and individuals with long sleep durations had a 36.2% lower risk of PD compared to those with short sleep durations.ConclusionDepression is significantly associated with the risk of PD in middle-aged and older populations. Our findings show a strong link between an unhealthy lifestyle and PD risk. This highlights the importance of addressing depression and avoiding unhealthy lifestyles in PD prevention.